The Interplay of Customary Law and Labor Regulations: A Comparative Legal Pluralism Study in Indonesia and Algeria - Febriharini, Mahmuda Pancawisma; Kunarto, Kunarto; Driss, Bakhouya (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This study examines the interaction between customary law and national labor regulations in Indonesia and Algeria through the lens of legal pluralism. The research is motivated by the persistent coexistence of formal state law and traditional practices in shaping employment relations, which is particularly evident in societies with strong communal and religious traditions. Both Indonesia and Algeria represent cases where historical legacies of colonialism, post-independence political choices, and enduring social structures have produced distinctive forms of legal pluralism in labor relations.Purposes of the Research: The purpose of this research is to compare how legal pluralism operates in the two countries to regulate employment relations, resolve labor disputes, and accommodate customary norms within national frameworks.Methods of the Research: This study applies a normative legal research method with a comparative legal approach. Primary data sources include statutory regulations such as the Indonesian Labour Law Number 13 of 2003 (as amended by the Job Creation Law 2020 and Law Number 6 of 2023) and the Algerian Labour Code (Law Number 90-11/1990), while secondary data are drawn from academic literature, case studies, and reports from international institutions like the ILO. Data were analyzed using a descriptive-comparative technique to identify similarities, differences, and integration patterns between customary law and national labor regulations.Results of the Research: The findings reveal that both Indonesia and Algeria institutionalize pluralism by formally recognizing certain customary practices, such as oral employment agreements in Algeria and community-based contractual practices in Indonesia. This novelty lies in demonstrating how pluralism is not merely a social phenomenon but also a legally recognized mechanism for regulating labor relations and dispute resolution. This study advances existing knowledge by showing that legal pluralism provides a flexible and context-sensitive framework for labor law, balancing global standards with local legitimacy.